Food, Tourism and Destination Differentiation: The Case of Rotorua, New Zealand - Steinmetz, Rose (Auckland University of Technology, 2010)
Policy makers, industry and researchers are paying considerable attention to the importance of the relationship between food and tourism in destination differentiation from competitors and in contributing to economic development. There is a vital role for food in broadening a destination’s appeal; increasing visitor yield; enhancing visitor experience; strengthening regional identity; and stimulating growth in other sectors. Thus, food contributes to the overall sustainable competitiveness of a tourism destination. Despite growing research interest in food and tourism, there is still work to be done to bring the relationship of these two elements into focus. In order to better understand the role that food plays in tourism destination differentiation and development this PhD research draws on globalisation theory, world culture theory, tourism development theory and network and cluster theory. Particular attention is paid to the role that global processes play in shaping regional competitiveness and resultant policy initiatives. The empirical focus of the research is on the case of Rotorua, New Zealand, located in the Bay of Plenty in the central North Island. Rotorua is one of the premier tourist destinations in New Zealand, however, on a range of socio-economic indicators it ranks poorly compared with other regions in the country. The region is rich in scenic resources and Maori cultural heritage and these are the main attractions of the district. With the exception of the traditional Maori hangi, the contribution of food in tourism has not been emphasized strongly by regional food/tourism stakeholders. This study argues that greater use of local food in the region’s tourism offers a means of potentially strengthening the district’s development and differentiation. A thorough content analysis of national and regional tourism organisation marketing on the Internet and in brochures reveals that food features prominently in the 100% Pure New Zealand Internet campaign and in a number of regional tourism promotions. Rotorua is shown to lag behind many regions in its use of food as a feature of the local tourism experience. Interviews with 50 tourism and food industry experts provide a range of insights into the issues associated with attempting to increase the role of food in tourism in Rotorua, and in New Zealand more generally. A variety of issues and constraints which work against developing the role of food in tourism are identified. The research highlights that there is little in the way of an identifiable regional cuisine in Rotorua. There is also lack of communication between local food and tourism stakeholders and an absence of effective networks. A variety of suggestions are then presented on ways to more effectively link food to tourism in Rotorua. The research highlights the importance of developing regional food network groups and the linking of food into local tourism strategies. The potential to better develop indigenous dimensions of food in tourism is also examined. Not every region can market themselves as ‘food tourism’ destinations but most have some potential to increase the role that local food plays in tourism and development. The Rotorua case shows that there is potential to use food as a tool to achieve destination differentiation and development in regions whose success and renown is based on attractions other than food.
Keywords: Regional; Differentiation; Qualitative; Tourism